2021
DOI: 10.3390/ijerph18094891
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Fascia Iliaca Compartment Block after Elective Total Hip Replacement: A Prospective, Randomized, Controlled Study

Abstract: Objective: An assessment of the feasibility of fascia iliaca compartment block (FICB) combined with nonopioid analgesics and patient controlled analgesia (PCA), oxycodone, in the perioperative anaesthetic management for elective total hip replacement (THR). Design: A randomised, single-center, open-label study. Setting: A single hospital. The study was conducted from October 2018 to May 2019. Participants: In total, 109 patients were scheduled for elective total hip replacement. Interventions: Postoperative FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
2
22
0
1
Order By: Relevance
“…In agreement with this study, Gola et al [18] evaluated the viability of FICB with nonopioid analgesics and patient-controlled analgesia (PCA), in the perioperative anesthetic management for elective total hip replacement. Gola's team disocered that the pain score in FICB group was statistically significantly less than the control group.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In agreement with this study, Gola et al [18] evaluated the viability of FICB with nonopioid analgesics and patient-controlled analgesia (PCA), in the perioperative anesthetic management for elective total hip replacement. Gola's team disocered that the pain score in FICB group was statistically significantly less than the control group.…”
Section: Discussionsupporting
confidence: 56%
“…Also, Deniz et al [16], support our results that, no adverse effect as nausea. In addition, Gola et al [18] found insignificant differences in complication.…”
Section: Per Our Results Stevens Et Almentioning
confidence: 94%
See 2 more Smart Citations
“…Needle insertion in the outside FICB approach is directed toward the inside, so that the direction of the inserted catheter is away from the lateral femoral cutaneous nerve, while the needle insertion direction of the inside FICB approach points to the outside, so that the indwelling catheter tip is closer to the lateral femoral cutaneous nerve ( 18 , 19 ). The lateral femoral cutaneous nerve block ratio was higher with less postoperative analgesia ( 20 22 ). The lateral femoral cutaneous nerve divides into anterior and posterior branches at about 5 cm below the anterior superior iliac spine, and the posterior branch moves to the posterior and inferior ear, and distributes to the skin near the greater trochanter of the femur.…”
Section: Discussionmentioning
confidence: 95%